A Conceptual Model for Teaching Social Responsibility and Health Advocacy: An Ambulatory/Community Experience (ACE) - Girard-Pearlman Banack, Jeannine; Albert, Mathieu; Byrne, Niall; Walters, Cassandra (Revue canadienne de l'éducation médicale, 2011)
Background: At a macro level, Social Responsibility and Social Accountability are explicit priorities for medical schools in Canada and internationally, although the advancement of this vision is still developing. At a micro level, Health Advocacy is important for physicians-in-training as well as practicing physicians. The conceptual model being proposed is that Social Responsibility is connected to mastering Health Advocacy. The University of Toronto Faculty of Medicine has 16 years of experience through a mandatory 4th year clerkship course entitled the Ambulatory/Community Experience (ACE) which from inception emphasized Social Responsibility and Health Advocacy. The objective of this retrospective study was to provide a model to support the acquisition of Health Advocacy and the development of socially responsible medical students. Methods: A conceptual model with three distinct elements: 1) ambulatory/community placements, 2) individual pedagogical approaches and 3) narrative, reflective assignments was applied. Results: The three elements of the model, all based on the five ACE learning domains (objectives) and embedded in CanMEDS type competencies, are effective and appear to support achievement of competency in Health Advocacy. Conclusion: A model which includes vetted ambulatory/community placements, individual pedagogical approaches, and narrative reflective assignments based on objectives with a Health Advocate perspective appears to encourage Social Responsibility in medical students.